Disciplinary Potential and Individual Choice: Reflections from Participatory Research on Oaxacan Intercultural Education. Issue 2 (15th December 2020) - Lebrato, Matthew
Abstract: This article reflects on the current status of participatory research in anthropology. I draw on my work at the Instituto Superior Intercultural Ayuuk (Ayuuk Intercultural University) in Oaxaca, Mexico to sketch some of potentials and pitfalls for participatory research during the preliminary, data‐collection, and postfield phases. My argument is that while anthropologists as individuals tend to find ways to connect meaningfully with collaborators in the field, the discipline does little to train, foster, or evaluate participatory research as a core element. Assigning participatory research to the status of a personal choice rather than a disciplinary hallmark saps anthropology's potential for meaningful engagement with a host of publics, not the least of which are the communities, groups, and networks of individuals with whom we conduct research. [decolonization, intercultural education, Latin America, participatory research, training and methods]